2020
DOI: 10.3390/md18010062
|View full text |Cite
|
Sign up to set email alerts
|

Fucus vesiculosus and Ascophyllum nodosum Ameliorate Liver Function by Reducing Diet-Induced Steatosis in Rats

Abstract: The Asian coastal communities have used the brown seaweeds Fucus vesiculosus and Ascophyllum nodosum since ancient times. Recently, some in vitro and in vivo studies have demonstrated their abilities in reducing risk factors for metabolic syndrome. Here, we analyzed the protective effect of a phytocomplex extracted from these seaweeds on the deposition of fat in the liver after the administration of a high-fat diet (HFD) to rats for five weeks. The administration of F. vesiculosus and A. nodosum led to signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 36 publications
3
16
0
Order By: Relevance
“…CVDs represent the main cause of death worldwide, with 422.7 million cases (according to a 2015 report), and approximately 18 million deaths [ 22 ]. Moreover, it has been estimated that hypertension is diagnosed in 40% of adults (aged >25 years), and the annual expenses due to the patients’ management and the loss of productivity due to heart disease in the USA are estimated to be around 200 billion dollars at least [ 4 ]. Noteworthy, Japanese and Korean people have one of the longest average life expectancies and display a lower risk of developing hypertension and cardiovascular diseases than other populations [ 23 , 24 ].…”
Section: Metabolic Syndrome Mechanisms and Comorbiditiesmentioning
confidence: 99%
See 3 more Smart Citations
“…CVDs represent the main cause of death worldwide, with 422.7 million cases (according to a 2015 report), and approximately 18 million deaths [ 22 ]. Moreover, it has been estimated that hypertension is diagnosed in 40% of adults (aged >25 years), and the annual expenses due to the patients’ management and the loss of productivity due to heart disease in the USA are estimated to be around 200 billion dollars at least [ 4 ]. Noteworthy, Japanese and Korean people have one of the longest average life expectancies and display a lower risk of developing hypertension and cardiovascular diseases than other populations [ 23 , 24 ].…”
Section: Metabolic Syndrome Mechanisms and Comorbiditiesmentioning
confidence: 99%
“…Several studies have demonstrated that many phlorotannins are also able to increase the glucose uptake by skeletal muscles and inhibit the protein tyrosine phosphatase 1B (PTP1B), which regulates the leptin and insulin signaling pathways, thereby improving insulin sensitivity [ 19 , 94 ]. Accordingly, many studies have reported that A. nodosum and F. vesiculosus display antidiabetic properties due to their phenolic-rich composition, and are able to decrease the postprandial blood glucose levels and insulin peak in various animal models of MS-related disorders [ 4 , 95 , 96 ]. Moreover, since postprandial “hyperglycemic spikes” could induce micro- and macro-vascular diseases, it is reasonable to hypothesize that these algal phlorotannins could be beneficial for CVD patients [ 97 ].…”
Section: Bioactive Compounds Of Brown Seaweedsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fucoidan is a water-soluble heteropolysaccharide, derived mostly from brown algae, such as Fucus vesiculosus (Figure 1) [1][2][3][4][5]. Recent studies have shown that the research on fucoidan mainly focuses on two aspects-one is to explore ways to increase the yield of fucoidan [6][7][8][9], while the other is to explore the various pharmacological activities of fucoidan [10][11][12], including anti-inflammatory [13,14], anti-tumor, anti-virus, hypolipidemic, antithrombotic, and so on [15], but less research exists on its mechanism.…”
Section: Introductionmentioning
confidence: 99%